Medial pedicled orbicularis oculi flap - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Resurfacing of the medial canthal region and bony nasal dorsum is a problem frequently encountered after tumor excisions. Traditional flaps used in this region from the glabellar and frontal areas are bulky, and donor site scar may be unsightly. A medial pedicled orbicularis oculi myocutaneous flap is an alternative. A total of 12 flaps have been used to resurface the defects secondary to basal cell carcinoma excisions, with a mean follow-up of 10 months. All flaps survived. The flap elevation is easy and fast, and the flap can be extended to the contralateral site when needed. The skin match is good and donor morbidity is minimal.
Keywords: MYOCUTANEOUS FLAP